Developmental Dysplasia of the Hip: How Many Risk Factors Are Needed? - Adelina Ionescu; Mihai-Codrut Dragomirescu; Alexandru Herdea; Alexandru Ulici (MDPI AG, 2023)
Developmental dysplasia of the hip (DDH) is a progressive condition that lacks clear diagnostic and management protocols, due to insufficient data. While some advocate for universal screening, others recommend using risk factors as landmarks. In this study, we aimed to assess the risk factors associated with DDH incidence among a large population. We conducted a retrospective single-center multifactorial study between January 2019 and March 2022, including 3720 children who were investigated anamnestically, clinically, and through an ultrasound scan. We classified them into two groups: the control group with 3300 healthy children and the study group with 420 newborns diagnosed with DDH. Our analysis identified several risk factors associated with DDH, including gender, prematurity, non-vertex birth presentation, oligohydramnios, gestational diabetes, maternal hypertension, family history, associated deformities, and swaddling. We found that every DDH patient had at least two risk factors. Based on our findings, we recommend that children who present two or more risk factors for DDH be mandatorily evaluated sonographically, as well as children with clinical signs. DDH screening is recommended for each newborn for the long-term benefits of early detection and treatment.